Unhealthy Work? The policy/-practice divide in Australian call centres - Lamm, F; Hannif, Z; Vo, A (ER Publishing Ltd, 2010)
Call centres have attracted the attention of researchers globally due to their implementation of new forms of work organisation and the implications these represent for the workforce. While there has been a great deal written on the poor working conditions within the call centre industry, and some discussion on the impact of these conditions on the health and safety of workers, there is still little known about the occupation health and well being policies and practices used in these workplaces. There has also been scant research on the health and safety experiences of call centre workers. This paper aims to address these gaps by examining whether the tasks performed and the occupational health and well being policies and practices in call centres lead to unhealthy outcomes for workers. A case study methodology is applied to explore these questions in two Australian call centres which highlight the diversity that exists in the industry. Key findings based on interviews with case study participants and key stakeholders indicate a misalignment between policy and practice, which represent various immediate and ongoing risks for employees. A number of policy concerns are raised through the data, particularly where negative occupational health outcomes can be associated with the lack of organisational compliance with employment legislation.